2017
DOI: 10.1136/bcr-2017-220592
|View full text |Cite
|
Sign up to set email alerts
|

Non-atherosclerotic aortic mural thrombus: a rare source of embolism

Abstract: A 54-year-old man presented to the emergency department with acute left-sided chest pain and left upper quadrant abdominal pain. He had a significant history of squamous cell carcinoma of the lung previously treated with right pneumonectomy who ; is currently receiving adjuvant chemotherapy with cisplatin. Physical examination was remarkable for tachycardia, hypertension and mild abdominal tenderness. CT angiography revealed an aortic mural thrombus in the ascending aorta and aortic arch without dissection, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Hypercoagulability caused by blood disorders, malignant neoplasms, anticancer therapy, hormonal therapy, collagen diseases, and pregnancy is associated with the development of thrombi. 1 , 2 In this patient, the level of homocysteine, which has atherogenic and prothrombotic properties, was high. Furthermore, because nutritional deficiencies including vitamin B deficiency are highly prevalent in patients with sustained heavy alcohol consumption, 7 an elevated blood homocysteine level can reflect a deficiency in folate, vitamin B 6 , or vitamin B 12 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Hypercoagulability caused by blood disorders, malignant neoplasms, anticancer therapy, hormonal therapy, collagen diseases, and pregnancy is associated with the development of thrombi. 1 , 2 In this patient, the level of homocysteine, which has atherogenic and prothrombotic properties, was high. Furthermore, because nutritional deficiencies including vitamin B deficiency are highly prevalent in patients with sustained heavy alcohol consumption, 7 an elevated blood homocysteine level can reflect a deficiency in folate, vitamin B 6 , or vitamin B 12 .…”
Section: Discussionmentioning
confidence: 72%
“…Several authors have reported successful results using anticoagulants, such as warfarin, for the treatment of aortic thrombi. 1 , 5 , 16 Marin-Acevedo et al 2 reported complete resolution of an ascending aortic thrombus using rivaroxaban. Although the optimal drug, dose, and duration of anticoagulation therapy are crucial, they are not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ascending aortic thrombus is a very rare source of embolic TIA or stroke without an associated aortic pathology, such as aortic dissection, atherosclerosis, or aortic aneurysm. There have only been prior case reports in the ascending aorta 1 , 2 and descending aorta. 3 The exact mechanism of thrombus formation in these patients is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…A hypercoagulable state and aortic disease are the main etiologies of AFT (1,2). In computed tomography angiography (CTA) of the aorta, AFT has been mostly found in the thoracic and abdominal aortas, while it is rarely found in the ascending aorta.…”
Section: Introductionmentioning
confidence: 99%